PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH - Musammah (CENDEKIA: Jurnal Studi Keislaman, 2020)
Abstract: The purpose of this study is to describe the application of the Problem Based Learning model to improve the activities and learning outcomes of Grade IV students on mixed count operations in SDN 1 Pekalongan, Gresik Regency. This research method is descriptive qualitative. The results of this study are an increase in student activity by 22.5% in the first cycle from 67% to 89.5% in the second cycle, teacher activity increased by 16.5% in the first cycle from 77.8% to 94.5% in cycle II, student learning outcomes increased 11% in cycle I was 74% to 85% in cycle II and the character of student responsibility increased by 11.01% in cycle I from 67.33% to 78.74% in cycle II.